The Effect of Using Fit Light Exercise in Some Physiological Indicators and Smash Shot for Badminton’s Players - Dakhill Hatem Al-Selmi, Abeer; S. Hosen, Mostafa. (International Journal of Psychosocial Rehabilitation, 2020)
The reason for applying the project is for the development of some physiological variables and skill performance using a device for the first time applied in Iraq to a sample of badminton players, and this device has a patent on 7/2/2019. An experimental method is used for a sample of 12 players from the Al-Orthodoxy club. The experimental group is applying the proposal technique, while the control group is instructed by the coach. The results of the research attribute to the role of the proposed exercises of fit light technology; thus, this technology has increased the attention and focusing of the sample and some physiological variables and smash shot skill. It has been concluded that the exercises using FitLight technology helped to improve their anaerobic abilities, as well as some physiological indicators. Furthermore, the exercises help to reduce the heart rate before and after the tension of the sample.